"WAIT-AND-SEE" MONETARY POLICY. (30th October 2017) - Lei, Xiaowen; Tseng, Michael C.
Abstract : This paper develops a model of the optimal timing of interest rate changes. With fixed adjustment costs and ongoing uncertainty, changing the interest rate involves the exercise of an option. Optimal policy therefore has a "wait-and-see" component, which can be quantified using option pricing techniques. We show that increased uncertainty makes the central bank more reluctant to change its target interest rate, and argue that this helps explain recent observed deviations from the Taylor Rule. An optimal wait-and-see policy fits the target interest rates of the Fed and Bank of Canada better than the Taylor Rule.